MENINGKATKAN NIAT TAMU BISNIS UNTUK MEMESAN HOTEL BINTANG EMPAT - Lilianto, Kent Julian; Hotna Marina Sitorus (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Business guests and leisure guests have different behaviors when choosing a hotel. This research aims to identify the factors that influence business guests to book four-star hotels. We purpose seven hypotheses to analyze the effect of online reviews, price, quality, location, business facilities, trust in the hotel, and perceived value on the intention to hotel booking. The proposed model is evaluated using partial least squares structural equation modeling (PLS-SEM), based on 250 data collected from business guests at four-star hotels in the City of Bandung, Indonesia. The results show that all seven hypotheses are supported: online reviews, price, quality, location, business facilities, trust in the hotel, and perceived value significantly influence the intention to book the hotel. The findings of this research are used to develop recommendations for one of the hotels in the city of Bandung that is facing challenges in increasing the occupancy rate of business guests.